Fa‘āliyatu Wasīlati Articulate Storyline li Tarqiyati Natā’iji Ta‘allumi al-Lughah al-‘Arabiyyah fī Maḍati al-Naḥwi - Nurlaila, Riza; Wahyudi, Muhammad; Nuruddin, Alfy Mamduh; Al-Ansori, Hamdan Fauzan (UAS PRESS, 2025)
This study aims to improve the effectiveness of learning Nahw material using engaging and interactive media in class 2 of Madrasah Aliyah Negeri 1 Kota Cimahi. Articulate Storyline is a type of interactive media accessible via smartphones or other devices, either online through links or offline, making it easier for students to access multimedia content. The research employed a quantitative True-experiment method with a Pretest-Posttest Control Groups design. The population comprised 252 students, with 72 students sampled from two classes: Religious and Science, each with 36 students. Data analysis involved Descriptive Statistics, Normality Test, Homogeneity Test, and Mann-Whitney Test using SPSS. The results showed significant differences in learning outcomes between experimental and control classes, with the experimental class achieving higher average scores (85.78 > 81.009). The Mann-Whitney test revealed a significance value of 0.004 < 0.05, confirming that the intervention effectively improved Arabic (Nahwu) learning outcomes.